Environmental Services: A New Approach Toward Addressing Sustainable Development Goals in Sub-Saharan Africa - Knight, Jasper (Frontiers in Sustainable Food Systems, 2021)
The physical environment provides resources and specific types of environmental services relevant to the maintenance of human livelihoods globally and with specific reference to sub-Saharan Africa, including soils, food and water systems. Previous studies on the shared nexus of such resources commonly view these as self-contained systems operating independent of their physical contexts provided by landscape-scale geomorphology and its related processes. This study critically examines the viewpoints adopted by such nexus studies with specific reference to sub-Saharan Africa, arguing that these studies are reductive, considering only the shared disciplinary overlap (nexus) and not their wider contexts, and are based on only a limited understanding of the workings of physical systems. This study argues that considering the attributes of the physical landscape and its provision of environmental services provides a broader and scientifically-informed context for understanding of interlinked issues such as relationships between soil–food–water systems. Framing such ‘nexus’ studies in this wider context can derive a better understanding of the connections between different elements such as soil, food and water, amongst others, and with respect to the United Nations’ Sustainable Development Goals. The concept of environmental services is therefore a more powerful tool to examine both the connections between physical and human environmental processes and properties in sub-Saharan Africa, and to address overarching environmental issues such as land degradation, soil erosion loss, water scarcity, and impacts of climate change.